FINANCIAL PERFORMANCE : ACCOUNTING PERSPECTIVE - Elfreda Aplonia Lau (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
This study aims to explain the purpose of financial performance from an accounting perspective. In addition, this study aims to bring up and explain how the measurement of financial performance from an accounting perspective. Problems in this study can be formulated as follows : First, What is mean by financial performance : Accounting perspective? Second, How to measure profit from Accounting perspective? The basic theory used in this study is the theory of Management Accounting with a primary focus on financial performance and profit concept. The hypothesis of this research are, First company's financial performance is profit, second profit measured by profit period, comprehensive profit, profit according to financial capital and profit according to physical capital. Analyzer used to support this research hypothesis is earnings report by Current Operating Concept (Earnings) / Profit period and All Inclusive Concept of Income (Comprehensive Income) The results support the first research hypothesis that what is mean by the company's financial performance from an accounting perspective is profit. Similarly, the results of this study support the second hypothesis that financial performance from an accounting perspective is measured using period profit, comprehensive profits, earnings by capital financial and physical capital. The concept of profit period is intended to measure the efficiency of a firm by comparing the current period's profit with the previous year's earnings. Comprehensive profits and period earnings are complementary. Comprehensive profits bring up the profitability, effectivity, and activity.